The Effect of Product Quality and Price on Customer Loyalty of Black Cough Medicine - Fauzan, Ricky; Widuri, Intan (Journal of Accounting and Finance Management, 2025)
This research aims to analyze the influence of product quality and price on customer loyalty of Indoplus brand Black Cough Medicine (OBH Syrup) produced by PT Indofarma Tbk, with a case study at Kimia Farma Pharmacy, Bandung Business Unit. Customer loyalty is a key factor in maintaining market share and encouraging business sustainability in the pharmaceutical industry, especially for cough medicine products. This research uses a quantitative approach with survey methods and data collection through questionnaires distributed to customers who buy and use OBH Syrup Indoplus products at Kimia Farma Bandung Pharmacy.  The variables tested in this research are product quality and price as factors that influence customer loyalty, which are analyzed using multiple linear regression.   It is hoped that the results of this research will provide useful insights for PT Indofarma Tbk in optimizing marketing and pricing strategies, as well as improving product quality to strengthen customer loyalty in the cough medicine market Key words: Product Quality. Price, customer loyalty.